L'organisation des savoirs enseignés et les difficultés d'apprentissage des élèves : l'effet du rapport au savoir de l'enseignant - Valérie Vincent (Nantes Université, 2012)
This article examines the actual pedagogical organization of school knowledge by teachers, while paying special attention to their way of dealing with the learning difficulties of their students. We will put to the test the hypothesis of an effect of the teacher's relationship to knowledge on this particular organization. Based on the first results of a doctoral research on the influence of teachers' relationship to knowledge on their pedagogical organization, this article uses observational data for one primary school teacher in Geneva, while teaching the prehistoric period. We address the problem by means of three exploratory and interdependent questions: 1) In what singular way does the teacher organize knowledge relating to prehistory within his or her teaching practice? 2) Within this singular organization, what is the form taken by the cognitive activity of students for whom the identitary, cognitive and epistemological relationship to knowledge may be problematic? 3) To what extent does the observed teacher's relationship to knowledge has an effect in his organization of instructed knowledge, on the meaning of school knowledge and finally, on his or her way of preventing and/or dealing with learning difficulties?